2022
DOI: 10.3389/fonc.2022.987704
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic significance of blood-derived circRNAs in NSCLC: Systematic review and meta-analysis

Abstract: BackgroundUsing blood-derived circular RNAs (circRNAs) may be an efficient tool for noninvasive fluid biopsy in diagnosing non-small cell lung cancer (NSCLC). However, no relevant systemic meta-analysis has been conducted so far to support the diagnostic value of using blood-derived circRNAs in NSCLC clinically. The aim of this study is to clarify the issue through a meta-analysis.MethodsA systematic search strategy was used to search relevant literature in the databases of PubMed, Web of Science, and Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…CircRNAs are a new class of non‐linear, single‐stranded and non‐coding RNAs with favorable biological stability and tissue cell specificity, which may be served as possible biomarkers for cancer diagnosis and prognosis 28 . Currently, the bulk of the researches suggested that circRNAs played vital role in regulating the progression of NSCLC 29,30 . Zhang et al discovered the up‐expressed circSATB2 in serumal exosomes from lung cancer patients, which was linked to the promotion of NSCLC proliferation, migration, and invasion 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are a new class of non‐linear, single‐stranded and non‐coding RNAs with favorable biological stability and tissue cell specificity, which may be served as possible biomarkers for cancer diagnosis and prognosis 28 . Currently, the bulk of the researches suggested that circRNAs played vital role in regulating the progression of NSCLC 29,30 . Zhang et al discovered the up‐expressed circSATB2 in serumal exosomes from lung cancer patients, which was linked to the promotion of NSCLC proliferation, migration, and invasion 31 .…”
Section: Discussionmentioning
confidence: 99%
“…28 Currently, the bulk of the researches suggested that cir-cRNAs played vital role in regulating the progression of NSCLC. 29,30 Zhang et al discovered the up-expressed circSATB2 in serumal exosomes from lung cancer patients, which was linked to the promotion of NSCLC proliferation, migration, and invasion. 31 Herein, we also noticed that circ_0000877 was up-regulated in NSCLC tissues and cells, circ_0000877 knockdown obviously prohibited NSCLC cell proliferation and accelerated apoptosis.…”
Section: Knockdown Of Circ_0000877 Inhibited Nsclc Tumor Growth In Vivomentioning
confidence: 99%